Recent advances of triglyceride catalytic pyrolysis via heterogenous dolomite catalyst for upgrading biofuel quality: a review - Ahmad Zamri, Mohd Faiz Muaz; Shamsuddin, Abd Halim; Ali, Salmiaton; Bahru, Raihana; Milano, Jassinnee; Tiong, Sieh Kiong; Fattah, Islam Md Rizwanul; Raja Shahruzzaman, Raja Mohd Hafriz (Multidisciplinary Digital Publishing Institute, 2023)
This review provides the recent advances in triglyceride catalytic pyrolysis using heterogeneous dolomite catalysts for upgrading biofuel quality. The production of high-quality renewable biofuels through catalytic cracking pyrolysis has gained significant attention due to their high hydrocarbon and volatile matter content. Unlike conventional applications that require high operational costs, long process times, hazardous material pollution, and enormous energy demand, catalytic cracking pyrolysis has overcome these challenges. The use of CaO, MgO, and activated dolomite catalysts has greatly improved the yield and quality of biofuel, reducing the acid value of bio-oil. Modifications of the activated dolomite surface through bifunctional acid–base properties also positively influenced bio-oil production and quality. Dolomite catalysts have been found to be effective in catalyzing the pyrolysis of triglycerides, which are a major component of vegetable oils and animal fats, to produce biofuels. Recent advances in the field include the use of modified dolomite catalysts to improve the activity and selectivity of the catalytic pyrolysis process. Moreover, there is also research enhancement of the synthesis and modification of dolomite catalysts in improving the performance of biofuel yield conversion. Interestingly, this synergy contribution has significantly improved the physicochemical properties of the catalysts such as the structure, surface area, porosity, stability, and bifunctional acid–base properties, which contribute to the catalytic reaction’s performance.